POLITENESS STRATEGIES OF ASSERTIVE ACTS BY INDONESIAN EFL LEARNERS IN CONVERSATION CLASS - Hastuti, Diyah Murti; Wijayanto, Agus (Universitas Muhammadiyah Metro, 2023)
The basis of human communication is the ability to conduct smooth conversations. It is currently highly demanded for people to be able to conduct conversations through politeness. In L2 learning, this has induced linguists and language educators to develop methods for enhancing L2 learners ability to communicate appropriately in L2. This paper is part of a descriptive qualitative study investigating the types of politeness EFL learners use during English conversations. It mainly analyzed the politeness strategies used by L2 learners with instructors during EFL activities. The participants were elementary students and the instructor. Observation and recording were the ways to collect the data. The data analysis process was through the politeness theory by Brown and Levinson (1987). This study revealed three politeness strategies; the students frequently used negative and positive politeness strategies. Whereas bald on record strategy was rarely used. The implication of the study was to build the students' good character. In addition, it could be beneficial for applying pragmatic theory to the ELT process in a particular course.